2021
DOI: 10.3390/brainsci11040455
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of Brain in Newborn with Congenital Diaphragmatic Hernia

Abstract: Congenital diaphragmatic hernia (CDH) is a severe pediatric disorder with herniation of abdominal viscera into the thoracic cavity. Since neurodevelopmental impairment constitutes a common outcome, we performed morphometric magnetic resonance imaging (MRI) analysis on CDH infants to investigate cortical parameters such as cortical thickness (CT) and local gyrification index (LGI). By assessing CT and LGI distributions and their correlations with variables which might have an impact on oxygen delivery (total lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 70 publications
(98 reference statements)
0
8
0
Order By: Relevance
“…A systematic review on the neurodevelopmental outcomes in CDH demonstrated that 16% of children born with isolated CDH have neurodevelopmental delay, mainly affecting motor function (13%) 12 . Furthermore, postnatal MRI studies have reported abnormal brain morphology, including enlarged extra‐axial spaces, intraventricular hemorrhage, ventriculomegaly, white matter injury, cerebellar hemorrhage, lower total maturation score, and hypogyria 13–17 . Some of these changes (enlarged extra‐axial spaces, ventriculomegaly, smaller cerebellar dimensions and delayed gyration) have also been described on fetal imaging; however, these studies show conflicting results 3,6,18,19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review on the neurodevelopmental outcomes in CDH demonstrated that 16% of children born with isolated CDH have neurodevelopmental delay, mainly affecting motor function (13%) 12 . Furthermore, postnatal MRI studies have reported abnormal brain morphology, including enlarged extra‐axial spaces, intraventricular hemorrhage, ventriculomegaly, white matter injury, cerebellar hemorrhage, lower total maturation score, and hypogyria 13–17 . Some of these changes (enlarged extra‐axial spaces, ventriculomegaly, smaller cerebellar dimensions and delayed gyration) have also been described on fetal imaging; however, these studies show conflicting results 3,6,18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, postnatal MRI studies have reported abnormal brain morphology, including enlarged extra-axial spaces, intraventricular hemorrhage, ventriculomegaly, white matter injury, cerebellar hemorrhage, lower total maturation score, and hypogyria. [13][14][15][16][17] Some of these changes (enlarged extra-axial spaces, ventriculomegaly, smaller cerebellar dimensions and delayed gyration) have also been described on fetal imaging; however, these studies show conflicting results. 3,6,18,19 All these raise the question whether neurodevelopmental problems in CDH are a consequence of postnatal events (surgery, intensive neonatal management with possible hypoxic episodes and hemodynamic instability) or if brain development is already compromised prenatally by the disease itself.…”
Section: Introductionmentioning
confidence: 99%
“…Neurodevelopmental impairment is an important complication in preterm infants with CDH 15,16,17,18,19 . Although the detailed mechanism is unknown, there are reports of central nervous system (CNS) abnormalities in CDH 20,21,22 . Congenital diaphragmatic hernia is a risk factor for hypoxic acidosis, which is a risk factor for CNS abnormalities during the disease.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The main finding is that the cingulate fissure, insular fissure and insular depth are significantly different in CDH fetuses compared with controls. The observation that up to 60% of infants with CDH shows signs of brain abnormalities on MRI performed before discharge from the neonatal intensive care unit (NICU) highlights the need to expand the study of the neurological aspects and pathophysiology of CDH in the prenatal period ( 2,14,(24)(25)(26)(27) ). The timing and mechanisms of neuropathological signs in children with CDH remain poorly studied and understood.…”
Section: Discussionmentioning
confidence: 99%